2D Materials in Light: Excited‐State Dynamics and Applications. Issue 5 (4th October 2019) - Li, Na; Wang, Qiang; Zhang, Hao‐Li
Abstract: The development of two‐dimensional (2D) materials have attracted increasing interest due to their unique structure and various potential applications such as opto‐electronic devices and photocatalysis. Our group have contributed to this exciting field by creating novel preparation methods for a various of 2D materials including transition metal dichalcogenides (TMDs), carbon nitrides and single elemental 2D materials from Group 15. Particularly, employing powerful time‐resolved spectroscopic techniques such as femtosecond transient absorption spectroscopy, we elucidated the excited‐state dynamics of 2D materials behind their outstanding performance in photocatalytic and photonic devices. Therefore in this account, we focus on the effective fabrication methods of 2D materials and their photoinduced excited‐state dynamics. Following the introduction in Part 1, we will summarize our novel strategies for fabricating 2D materials (Part 2 ). Then in Part 3 we will introduce the instrumentation for exploring the photoinduced excited‐state dynamics of the 2D materials spanning a wide time scale from ultrafast fs to slow ms . Part 4 details the applications of the 2D materials in photocatalysis and nonlinear optics determined by their excited‐state physics and chemistry. Part 5 of perspectives summarizes a few future trends of 2D materials on a series of issues like fabrications, dynamic investigations and photonic optoelectronic applications. Collective efforts through researchers from interdisciplinary fields are expected to further push the exciting territory towards a new horizon. Abstract : This personal account gives a summary of our recent progress on the effective fabrication methods of 2D materials, their photoinduced excited‐state dynamics and pertinent applications.